A study of surface swelling caused by graphitisation during pulsed laser ablation of carbon allotrope with high content of sp ³ bounds - Cadot, G.B.J.; Billingham, John; Axinte, Dragos A. (IOP Publishing, 2017)
Experiments and theory are employed to investigate the laser ablation of boron doped diamond and tetrahedral amorphous carbon using nanosecond pulses. For a single pulse at low values of fluence, the laser induces a swelling of the surface due to graphitisation, whilst a high level of fluence leads to recession of the surface due to vaporization. To understand and investigate the underlying phenomena during the diamond-laser interaction, a model has been developed to reliably and quickly predict the behaviour of the surface and the thickness of the heat affected zone. The model is based on conservation of heat and mass during the laser-workpiece interaction. It consists of a one-dimensional system of non-linear equations that models the material heating, evaporation, graphitisation and plasma shielding. There is excellent agreement between numerical and experimental results for the position of the interfaces up to a high laser fluence. This model is the first to investigate the ablation of diamond that is able to capture surface swelling due to the graphitisation of the diamond layer, the graphite thickness and the amount of ablated material within a single framework. Furthermore, the model provides a novel methodology to investigate the thermal stability of diamond-like carbon films. The activation energy for tetrahedral amorphous carbon is obtained using the model with an accuracy of 3.15+1.0−0.22 eV.